Decomposition of 14C-labelled plant material under field conditions - Paul, E. A., author; Shields, J. A., author; Agricultural Institute of Canada, publisher (Colorado State University. Libraries, 1973)
Mature, uniformly labelled (14C, 15N), chopped, wheat straw incorporated in the plow layer of a Brown Chernozemic soil and a Gray Wooded soil was allowed to decompose in the field. Labelled grass material (14C) was added to the surface of an adjacent virgin Brown Chernozemic soil. After 4 yr of normal cropping practices, one-fifth of the C of added straw remained in the Brown soil and one-sixth in the Gray Wooded. The initial decomposition rate of straw was retarded in plots under wheat as compared with those under fallow. Decomposition of labelled grass was initially dependent on sufficient rainfall to compress it to the soil surface. When winter periods are excluded from the time scale, the half-life of resistant straw components or soil organic matter derived from the straw was equivalent to 24 mo in Gray Wooded soil and 48 mo in Brown soil. Resistant grass material decomposed more slowly with a half-life of 96 growing mo. Distribution of labelled C among the various fractions of soil organic matter after different periods of time was investigated. The rapid decline of labelled straw from the fraction that floated in water, the high specific activity of fulvic acid, coupled with fluctuations in humic acid and the fraction <0.04 μ suggested a higher degree of biological activity in the Gray Wooded soil. In the Brown soil, the major transfer of labelled C was from the floated fraction to the humin (>0.2 μ) suggesting that the rate of decomposition was controlled to a greater extent by abiotic factors.
Keywords: litter decomposition; climatic zones; wheat straw; crop residues; erosion resistance; soil structure; soil organic matter